Mental health during the COVID-19 quarantine in five countries - Erika Yohanna BEDOYA CARDONA (Asociatia de Biosiguranta si Biosecuritate, 2021)
Introduction. As part of the holistic concept of health, mental health can be focused on prevention of contagion and coping with the disease and its consequences in the context of the current COVID-19 pandemic. The present study describes, compares, and analyzes the association of the impact of the event, perceived stress, coping strategies, emotional regulation, and sociodemographic characteristics during the quarantine in various countries.